Ambition for soil organic carbon sequestration in the new and updated nationally determined contributions 2020- 2021: Analysis of agricultural sub-sectors in national climate change strategies - Rose, Sabrina; Khatri-Chhetri, Arun; Stier, Milena; Wiese-Rozanova, Liesl D.; Shelton, Sadie W.; Wollenberg, Eva Karoline; Dittmer, Kyle (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Key messages - The share of countries that referenced soil organic carbon (SOC) in new and updated NDCs has increased since the previous round of NDCs. - Among the top 10 countries with the highest mitigation potential for SOC in croplands and grasslands, 6 referred to SOC in mitigation measures. - Among the top 10 countries with the highest mitigation potential in wetlands, 5 referred to wetlands in mitigation measures. - SOC commitments that demonstrated high standards, which may indicate options for other countries, included quantified outcomes, information on reference levels of indicators, mitigation potentials, and policies. - Specification of sub-sector actions in NDCs can improve eligibility for climate finance, but this level of detail can reduce countries’ flexibility for meeting their NDC targets and countries often lack affordable, robust monitoring, reporting, and verification (MRV) systems.